Biodiesel science and technology : from soil to oil - Bart, Jan C. J. (Woodhead Publishing in energy ;, 2010)
"Biodiesel production is a rapidly advancing field worldwide, with biodiesel fuel increasingly being used in compression ignition (diesel) engines. Biodiesel has been extensively studied and used in developed countries and is increasingly being introduced in developing countries, especially in regions with high potential for sustainable biodiesel production. Biodiesel Science and Technology provides a comprehensive reference on the technological developments involved in improving biodiesel quality and production capacity that are crucial to the future of the industry. This book begins by systematically reviewing feedstock resources and vegetable oil formulations, including the economics of vegetable oil conversion to diesel fuel. It also covers emerging energy crops for biodiesel production. The book then discusses the transesterification process, including chemical (catalysis) and biochemical (biocatalysis) processes, with extended coverage of industrial process technology and control methods and standards for biodiesel fuel quality assurance. Final chapters cover the sustainability, performance, and environmental issues of biodiesel production as well as routes to improve glycerol by-product usage and the development of next-generation products."--Publisher's description